Design And Development Of Linear DC Motor With Constant Thrust For Household Food Processing Application - Mat Isa, Siti Zulaika (2018)
Nowadays,technologies in food processing applications have grown rapidly to replace the traditional devices. Traditional methods are no longer practical as they require a lot of energy and longer time which will affect the productivity.In the case of tart and samperit,the traditional device has been replaced by modern technology such as the conventional linear DC motor (LDM).Therefore, the conventional LDM could be used to solve issues in traditional devices.Nevertheless,a simple and portable LDM that could produce a constant thrust with longer displacement is required nowadays especially by the small entrepreneurs.Moreover,conventional LDM has another drawback such as only suitable for short displacement. Previously,Typical Linear Actuator (TLA) had been introduced to solve several issues in conventional LDM. Basically,TLA use rotational motor connected to gears and ball screws.However,TLA is not in portable size because the assembly of TLA requires more space to protect the food material from gears,ball screw and grease.Thus,this research proposed a new type of linear DC motor that could produce constant thrust characteristics with longer displacement.The main objective of this research is to propose and analyze new LDM with constant thrust characteristics for food processing application.The modeling involves mathematical calculation using Permeances Analysis Method (PAM) and simulated by Finite Element Method (FEM).There are several parameters in LDM is varied for achieving longer displacement.A prototype of a new LDM is fabricated and measured for result verification.The results show small percentage difference between PAM with FEM and measurement.As a conclusion,this research has provided guidelines for designing LDM with constant thrust capability.